Capital Structure and Profitability of Public and Government Banks in Nepal - Shrestha, Sanjay (Journal of Economics and Management, 2024)
The study will examine how capital structure influences Nepalese public and government bank profitability. The study's statistical analysis utilizes secondary data. Descriptive and casual comparative analysis utilizing bank website data and correlations and multiple regression models for hypothesis testing was done using software. The study sampled 6 public banks and 2 governments from the population. The capital structure and profitability were examined as a cause-and-effect connection utilizing informal comparative study. This study uses NIM as a dependent variable and leverage ratio, bank size, liquidity ratio, and capital ratio as independent variables. Mean, standard deviation, correlation, multiple regression model, and hypothesis testing are statistical methods. Excel and SPSS assess such variables. Leverage Ratio boosts Public Bank NIM but not significantly. Bank Size negatively affects NIM somewhat. NIM and Liquidity Ratio are positively correlated. Public bank NIM is little affected by capital ratio. Leverage Ratio and bank size negatively affect Nepal's government banks' NIM. NIM positively and insignificantly impacts Liquidity Ratio. Capital ratio positively affects government bank NIM. Banks should recognise other variables' importance.